Characterisation of choroidal morphological and vascular features in diabetes and diabetic retinopathy. Issue 8 (5th January 2017) - Gupta, Preeti; Thakku, Sri Gowtham; Sabanayagam, Charumathi; Tan, Gavin; Cheung, Chui Ming Gemmy; Lamoureux, Ecosse L; Wong, Tien-Yin; Cheng, Ching-Yu
Abstract : Aim: We aimed to characterise specific morphological and vascular features of the choroid in Indian adults with diabetes and diabetic retinopathy (DR). Methods: Consecutive participants from the Singapore Indian Eye Study's 6-year follow-up examination underwent choroidal imaging using spectral domain optical coherence tomography (OCT) with enhanced depth imaging. Raw OCT images were loaded on a custom-written application on MATLAB that enabled delineation for detailed morphological and vascular analyses. Multiple linear regression analyses were performed to assess differences in choroidal characteristics by diabetes DR. Results: Of the 462 recruited participants, 273 had no diabetes (mean age was 60.1±6.8 years), 100 had diabetes but no DR (61.8±7.4 years) and 89 had DR (62.4±6.0 years). In multiple regression analysis, after accounting for relevant confounders, compared with those without diabetes, participants with diabetes had significantly thinner mean choroidal thickness (CT; mean difference (MD)=−25.19 µm, p=0.001), smaller choroidal volume (MD=−0.23 mm 3, p=0.003), more inflection points (MD=1.78, p<0.001) and lesser choroidal vascular area within the foveal (MD=−0.024 mm 2, p=0.001) and macular (MD=−0.095 mm 2, p<0.001) regions. Among the diabetic group, subjects with DR had significantly thicker mean CT (MD=25.91 µm, p=0.001), greater choroidal volume (MD=0.24 mm 3, p=0.009), lesser inflection points (MD=−0.478, p=0.045) and greater choroidal vascular area at foveal (MD=0.016 mm 2, p=0.019) and macular (MD=0.057 mm 2, p=0.016) regions, compared with those without DR. Conclusions: Choroidal morphology and vasculature were altered in Indian adults with diabetes and DR. These findings may provide insights into choroidal changes in diabetes and DR.